Pengaruh Pertumbuhan Perusahaan, Prediksi Kebangkrutan dan Opini Audit Going Concern Tahun Sebelumnya Terhadap Pemberian Opini Audit Going Concern - Gina Septiana; Eka Khausnul Khatimah (Fakultas Sastra Universitas Ekasakti, 2021)
Going concern audit opinion is an opinion issued by a company regarding the feasibility of its company's financial statements to see the future. This study aims to examine company growth, bankruptcy predictions and previous year's going concern audit opinion on the provision of Going Concern audit opinion on manufacturing companies listed on the IDX. This study uses a sample of manufacturing companies listed on the IDX in 2015-2019. Based on positive sampling, the number of manufacturing companies used in this study were 57 companies. Hypothesis testing uses logistic regression using the Spss 23 program. The results of this study indicate that company growthas going concern audit opinion, bankruptcy prdition has a significant negative effect going concern audit opinion and previous year”s going concern audit opinion has a significant positive effect on going concern audit opinion